The causal relationship of business innovation training and development, and job satisfaction of SME manufacturing in Palembang - Afriyadi Cahyadi (Universitas Hayam Wuruk Perbanas, 2015)
The aim of this research is to explore causal relationship among business innova-tion, training and development, and job satisfaction of micro and small manufactur-ing enterprises’ managers in Palembang city South Sumatera. An explanatory study uses path analysis to explain quantitative data. Data were collected from 335 sample managers of the enterprises by distributing self-developed questionnaires. The method of considering quantity of sample is random sampling. The results show that innovations have an effect on training and development, and training and de-velopment has a significant effect on job satisfaction. On the other side, innovations have no effect on job satisfaction. Innovations include raw materials, production processes and products offered. Job satisfaction include feelings of pleasure and enjoy, feeling calm and not be concerned about, do not ignore the feelings of the faithful, and the feeling of belonging and defend jobs.